Mexico, 1967: The critical Dialogue between Leopoldo Zea and Luis Villoro about Philosophy, Engagement, and Circumstances - Beltrán García, Iver A. (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This paper provides an analysis, an interpretation and an assessment of the issues and points of view discussed in a 1967 round table in which Leopoldo Zea, Luis Villoro, Alejandro Rossi, Abelardo Villegas and José Luis Balcárcel took part, as well as in the subsequent debate. Outstanding topics of this event are the relationship between philosophy and ideology, between philosophy and reflection on one’s own circumstances, and between philosophy and professionalism, based on the participations and texts of these philosophers. The relevance of the paper lies on the enduring interest of the involved issues, stances, and arguments; on the hermeneutical keys contributing to a better appreciation of the Zea’s and Villoro’s work; and on the reflection that it raises about the nature of philosophical dialogue and philosophical communities.